Comparação dos efeitos de duas frequências de aplicação da fotobiomodulação no rejuvenescimento facial: ensaio clínico controlado, randomizado e duplo cego - Bragato, Erick Frank (2022)
Studies have demonstrated the benefits of photobiomodulation for facial rejuvenation, especially with the use of red LED. However, there is still a high level of variability in the dosimetric parameters and frequency of application. This study compared the effects of FBM with a red LED mask (660nm ± 10 nm , 6.4 mW/cm², 8.05 J/cm², 5.02 mW, 21 min) on facial rejuvenation using 2 application frequencies through qualitative and quantitative assessments. One group received 3 weekly applications for 4 weeks, totaling 12 sessions (G1) and the other group received 2 weekly applications for the same period (G2), totaling 8 sessions. The control group (G3) received simulated photobiomodulation twice a week for 4 weeks. The study involved 95 female participants aged between 45 and 60 years, in the menopausal phase, who were unaware of their allocation in the groups. For the qualitative analyses, carried out before and after the end of the treatments, a photographic assessment scale ( Wrinkle Assessment Scale – WAS) was used, completed by 3 specialists (blinded in relation to the experimental group and period of photographing) and the assessment of the level of satisfaction of the participants with their face (Face-Q questionnaire). The same photographs used for the WAS were used to measure the wrinkles in the frontal, glabellae, right and left periorbital regions using Image J software by a blind researcher in relation to the experimental group and period of photographing. The depth, width and area of frontal wrinkles were evaluated through measurements of facial impressions by optical coherence tomography (OCT). Data were statistically analyzed with a significance level of 5%. In the Wrinkle Rating Scale (WAS) there were no statistically significant differences between the groups. As assessed by Image J, there was an improvement in the length of glabellar and right periorbital wrinkles in both FBM treatment groups (p<0.001) compared to the control group. By OCT, there was a decrease in the width of the frontal wrinkle by 12.5% and 8.4% in groups 1 and 2 respectively, with statistically significant differences (p=0.04). But the comparison with the control group (G3) showed no statistically significant difference (p=0.858). The patients' satisfaction rates by the FACE-Q were 79.6% and 73.4% in groups 1 and 2 respectively, with statistically significant differences in relation to the control group (G3) (p=0.001 and p=0.034). In qualitative evaluations, this work showed that the use of red LED for 8 or 12 sessions is able to significantly increase the level of satisfaction of patients with regard to their facial appearance, but this improvement cannot be identified in the photographic evaluation scale by specialists . In the quantitative evaluations, using photos, a decrease in wrinkle length was observed in some regions, while in the OCT evaluation, no difference was observed in the frontal wrinkle. The union of methodologies for evaluating aesthetic gains can bring a more global analysis of the effects obtained by photobiomodulation.